Dietary Vitamin K and Association with Hepatic Vitamin K Status in a Yup'ik Study Population from Southwestern Alaska. Issue 3 (29th December 2017) - Au, Nicholas T.; Ryman, Tove; Rettie, Allan E.; Hopkins, Scarlett E.; Boyer, Bert B.; Black, Jynene; Philip, Jacques; Yracheta, Joseph; Fohner, Alison E.; Reyes, Morayma; Thornton, Timothy A.; Austin, Melissa A.; et al.
Abstract : Scope: The relationship between dietary vitamin K and plasma PIVKA‐II concentration, a biomarker of hepatic vitamin K status, in a Yup'ik study population in southwestern Alaska is investigated. Methods and results: A total of 659 male and female, self‐reported Yup'ik people, ≥14 years of age, were enrolled. Blood is collected for genotyping and plasma PIVKA‐II biomarker analysis. A Yup'ik‐specific dietary food frequency questionnaire is used to assess vitamin K intake. Among the participants, 22% report not consuming foods rich in vitamin K during the past year and 36% have a PIVKA‐II concentration ≥ 2 ng mL –1, indicating vitamin K insufficiency. The odds of an elevated PIVKA‐II concentration are 33% lower in individuals reporting any versus no consumption of vitamin‐K‐rich foods. The association is significant after adjusting for CYP4F2*3 genotype. Tundra greens are high in vitamin K1 content, but an exploratory analysis suggests that subsistence meat sources have a greater effect on vitamin K status. Conclusions: A substantial proportion of the Yup'ik population exhibits vitamin K insufficiency, which is associated with low consumption of vitamin K rich foods and which might affect an individual's response to anticoagulant drugs such as warfarin that target the vitamin K cycle. Abstract : The inter‐relationship between dietary vitamin K and PIVKA‐II status in a Yup'ik study population is studied. γ‐Carboxylation of Glu to Gla residues on Factor II and other clotting factors is modulated by dietary intake of vitamin K and by CYP4F2‐mediated metabolism to K‐acid metabolites. Low dietary intake of vitamin K reduces the hepatic pool of the active γ‐glutamyl carboxylase cofactor, vitamin K hydroquinone. A high frequency of the low activity CYP4F2*3 allele in the Yupik population conserves vitamin K and reduces the risk of elevated PIVKA‐II. Dietary vitamin K intake, from both plant and marine sources, as well as CYP4F2 genotype may independently modify the pharmacodynamic effect of warfarin, an inhibitor of vitamin K oxidoreductase (VKOR) and the vitamin‐K‐dependent clotting factor synthesis cycle.